Pengembangan Modul Pembelajaran Tema Sistem Tata Surya Pada Siswa Kelas IV SDN Gedongombo 6 Kabupaten Tuban - Wiratama, Novialita Angga; Agustin, Agustin; Agustin, Ina (Universitas Nusantara PGRI Kediri, 2021)
The curriculum is always changing according to developments in science and technology. Curriculum design in education needs to be done to answer the needs of society and the challenges of changing times. The curriculum is a guide in achieving the objectives of implementing the teaching process. The SD learning process in implementing the 2013 curriculum is carried out in an integrated manner with the theme of linking between subjects so that it is expected to provide meaningful learning experiences for students. Teachers determine student success in learning so that superior human resources are created through the educational process. The module is a printed teaching material that teachers can use to present learning material. This study developed a module with the theme of the solar system, sub-theme Change in the Appearance of Celestial Objects in SDN Gedongombo 6, Semanding District, Tuban Regency in fourth grade students. The research used is the development of the learning module. The research procedure uses the Four-D model according to Thiagarajan. The data collection instrument for this module development research consists of an assessment instrument for the subject matter expert learning module, an assessment instrument for the linguist learning module, an assessment instrument for the learning module for media experts, student questionnaires, and a teacher questionnaire. From the results of module development that have been validated by experts, it is obtained data that the module still needs reforms. Learning data and information results in the effectiveness of learning. Evidence of the final test data using the module shows the achievement of KKM 75 by 21 students out of 25 students.